The Prevalence and Magnitude of Social Loafing, and Biographical Influences, in a Team - Based Organizational Setting - Dhashendra Naicker; Sanjana Brijball Parumasur (Journal of Economics and Behavioral Studies, 2018)
This paper assesses the prevalence and magnitude of social loafing in a team-based organizational setting as social loafing has the potential to threaten and disrupt the effectiveness of teams. The presence of social loafing is evaluated in terms of perceived co -worker loafing, nature of tasks, visibility of contribution, group size, individual outcomes and rewards and, group cohesiveness. Biographical influences on perceptions of the factors having the potential to influence social loafing are also assessed. A consensus sample of 80 employees formed part of the sample. Data was collected using a self- developed, precoded questionnaire whose psychometric properties (validity and reliability) were assessed using Factor Analysis and Cronbach’s Coefficient Alpha respectively. The results indicate that social loafing does exist in the organization and is sparked by various factors which in descending level are perceived co -worker loafing, visibility of contribution, nature of tasks, group size, individual outcomes and rewards and, group cohesiveness. Furthermore, social loafing is moderate in magnitude and is not influenced by biographical variables (gender, age, marital status, tenure) except for the influence of age on individual outcomes and rewards. Recommendations are presented, which when implemented, have the potential to reduce the prevalence and magnitude of social loafing in a work environment.